Integrating the Content of Surah Al Baqarah verse 177 in Islamic Education to Realize Moral Character - Maretha Cyndiana Putri Valentine; hafidz hafidz; Deswita Rahmatiyas Avita; Diksi Atha Putra; Revina Ayudinata; Anisa Ayu Sholikah; Revanicha; Muhammad Radika Aryansyah (Bulletin of Islamic Research, 2025)
The main problem in this study is how the virtue values taught in Surah Al-Baqarah verse 177 can be applied as a guideline for the formation of individual character in the context of Islamic education. This study uses a qualitative method with a thematic interpretation approach, studying in depth the content of verses through the analysis of the Qur'an text and supporting literature. The results of the study show that this verse emphasizes the importance of true virtues which include faith, deeds, and noble morals, such as patience, honesty, trust, and humility. These values contribute to the formation of character that includes an individual's relationship with God, others, and himself. The implementation of these values in Islamic education can create intellectually intelligent individuals with noble character, as well as build a harmonious society and obey Allah.